Demographic transformation and the influence of eleven selected socio-demographic variables on the face validity of an engineering English for specific purposes approach at a South African university - Moyo, J.; Mann, C. C. (South African Journal of Higher Education, 2021)
In English for Specific Purposes (ESP), as accountable education, face validity, which could be an undesirable “negative” or a desirable “positive”, is one of the ways in which we determine the learners’ attitudes toward, and probable consequent motivation for, ESP learning programmes. In this study, we sought to explain the reactions of the 226 first year Engineering student respondents to Likert items by their sociodemographic characteristics. We measured and classified as an undesirable “negative” (if the mean was < 3.50), or a desirable “positive” (if the mean was ≥ 3.50), the face validity generated by eleven sociodemographic characteristics for an ESP approach employed in the design and delivery of a compulsory ESP module (Engineering Communication) at a university in South Africa’s Gauteng Province. We subjected the data to statistical significance testing with the ANOVA suite of inferential statistics to identify statistically significant relationships between the sociodemographic variables and the face validity variables, of which 20 were confirmed, and then measured the variance (influence) in the latter that could be associated with the former. The aggregate influence explainable by the sociodemographic variables was an eta2 of .908 (90.8%), of which High School Type (19.8%) recorded the most, and Engineering Work Experience (1,7%), the least. Whereas, Race was associated with the most “negative” influence, the Black1 and White groups were practically indistinguishable in attaining unequal, but “negative”, scores. When we compared the sample demographic statistics to available institutional and national statistics to check for demographic transformation, the statistics suggested that the research university was transforming demographically at a fast pace, given its history.